YOGA’S INCREASING SIGNIFICANCE FOR POST COVID-19 HEALTH - Meenu; Malik, Ishwar Singh; Bai, Kerosta (INTERNATIONAL JOURNAL OF RESEARCH PEDAGOGY AND TECHNOLOGY IN EDUCATION AND MOVEMENT SCIENCES, 2023)
The COVID-19 pandemic and related lockdown measures have completely disrupted work-life balance. People have been imprisoned for months in their homes that double as offices due to restrictions in numerous European nations and other places across the world. The physical and mental health of people has been under tremendous strain as a result, and yoga and gym facilities had to close. The International Day of Yoga (June 21) honours both the physical and mental benefits of this age-old Indian practise as well as the People have been imprisoned for months in their homes that double as offices due to restrictions in numerous European nations and other places across the world. The physical and mental health of people has been under tremendous strain as a result, and yoga and gym facilities had to close. The Covid-19 Pandemic and related lockdown measures have completed disrupted work-life balance. Yoga can help you manage the solitude and ambiguity of the lockdown while also maintaining your physical health. An increasing number of users have turned to online yoga sessions to regain balance and strength during lockdown and after it has ended. It demonstrates the increased significance of yoga for wellbeing following COVID-19.